1962
DOI: 10.1021/ac60182a027
|View full text |Cite
|
Sign up to set email alerts
|

Precision in X-Ray Spectrochemical Analysis. Fixed-Time vs. Fixed-Count.

Abstract: In the case of the derivative of 2methyl-l-butanethiol, a considerable discrepancy exists (20°). Since the melting point value obtained seems to agree quite well with that of the isomeric 1-pentanethiol, it was thought that perhaps the Eastman sample was mislabeled. However, a mixed melting point determination of the derivative of 1-pentanethiol and the supposed 2methyl-l-butanethiol gave a substantial depression. Furthermore, an intensive NMR study of the questionable derivative, the mercaptan from which it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1964
1964
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…This is obtained by combining a proper setting of the nucleonics clock with the number of repetitions of the count determination. The results are quite different from those given by Parrish (1956) or Birks and Brown (1962) who compared the fixed-time and the fixed-counts modes. Their conclusions have already been discussed by Gaylor (1 962).…”
Section: Time Optimizationcontrasting
confidence: 99%
“…This is obtained by combining a proper setting of the nucleonics clock with the number of repetitions of the count determination. The results are quite different from those given by Parrish (1956) or Birks and Brown (1962) who compared the fixed-time and the fixed-counts modes. Their conclusions have already been discussed by Gaylor (1 962).…”
Section: Time Optimizationcontrasting
confidence: 99%
“…A comparison of the two methods is therefore impossible unless the criterion used for comparison is clearly stated. Birks and Brown (1962) have shown that in routhe spectroscopic measurement of line and background intensitis, the fixed-time method is more convenient since it is faster than the fixed-count method and only slightly less accurate, In order to compare the two methods, they assumed that the same number of counts are accumulated in the two methods for the determination of TI. Here it has been shorn that this conc!usion is CGiiKt evea when account is taken @f the difference in total time required for the determination of the intensity Z by the two methods.…”
Section: Comparison Of the Two Methodsmentioning
confidence: 99%
“…There have been articles discussing precision, accuracy, and errors (2, 63,141,142,144) and failure analysis (106). There have been applications in wet analysis (43,62), spectrographic and optics work (30,88,110), and radiochemistry techniques (76,135).…”
Section: Review By Fields Of Interestmentioning
confidence: 99%